2012
DOI: 10.1177/0884533612466112
|View full text |Cite
|
Sign up to set email alerts
|

Clear Liquid Diet vs Soft Diet as the Initial Meal in Patients With Mild Acute Pancreatitis

Abstract: In patients with mild acute pancreatitis, a soft diet as the initial meal is well tolerated and leads to a shorter total length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Also, none of the patients receiving light diet in the study by Rajkumar et al were readmitted in the 30 days following discharge [8]. However, the generalizability of the data from this study is questionable, given that 90% of AP cases were of alcoholic etiology and the study population had an 11:1 male to female ratio, which is clearly not representative of the general population.…”
Section: Lightmentioning
confidence: 48%
See 3 more Smart Citations
“…Also, none of the patients receiving light diet in the study by Rajkumar et al were readmitted in the 30 days following discharge [8]. However, the generalizability of the data from this study is questionable, given that 90% of AP cases were of alcoholic etiology and the study population had an 11:1 male to female ratio, which is clearly not representative of the general population.…”
Section: Lightmentioning
confidence: 48%
“…No difference in tolerance was found between the two arms in either study, suggesting that a light diet is as safe as the current conventional protocol. In contrast to the study by Jacobson et al, both studies found that patients starting on a light diet had a significantly reduced length of hospitalization (an average difference of 2 days in both studies) [7,8]. It is interesting to note that, although discharge was ultimately at the discretion of the treating team, both these studies had pre-defined discharge criteria included in their protocol, following the tolerance of a full diet.…”
Section: What To Feedmentioning
confidence: 83%
See 2 more Smart Citations
“…A meta-analysis of three RCTs with 326 patients with mild acute pancreatitis showed that a solid diet reduced the length of hospital stay, compared to a liquid diet, but did not affect the rates of recurrent pain after refeeding [90]. Decreased length of hospital stay has also been shown in the most recent RCTs with a solid as opposed to a liquid diet in mild acute pancreatitis [91,92]. One recent RCT compared early nasogastric tube feeding to nothing per os in patients with mild-to-moderate acute pancreatitis and found that the patients in the nasogastric tube feeding group had significantly less abdominal pain, need for opiates and refeeding intolerance but did not decrease length of stay [93].…”
Section: Nutritionmentioning
confidence: 84%